Enhancing accessibility to web mapping systems with technology-aligned adaptive profiles - Delfos, Jacob; Veenendaal, Bert; Tan, Tele (Taylor & Francis, 2013)
Web-based geographic information systems have advanced rapidly on the back of web-based technologies, increased bandwidths and access to Digital Earth imagery and functionality. However, these advances are causing its capabilities to slowly overtake those of end-users. Additionally, the introduction of non-desktop devices such as smartphones, tablets and netbooks is starting to undo progress made towards standardisation of web-based technology. Large variations in screen sizes, computational power, bandwidth, and operating environments are once again introducing the need to ensure software remains functional across different platforms, standards-compliant or not. These two issues highlight the need for a mechanism to tune content and capability to end-users and their environment, to prevent information and complexity overload in a field already troubled by poor usability, while promoting cross-platform compatibility. This paper proposes the use of adaptivity to accommodate for users from different backgrounds accessing web mapping systems in different technical environments. It describes adaptive profiles aligned to the finite number of states a system can adopt, rather than the limitless range of user or environment characteristics that cannot be adapted to. Each profile consists of a combination of adaptive states comprising functionality, information detail, or technical demands to optimise for individual users or technical environments.